hetN and patS Mutations Enhance Accumulation of Fatty Alcohols in the hglT Mutants of Anabaena sp. PCC 7120 - Munawaroh, Heli Siti Halimatul; Apdila, Egi Tritya; Awai, Koichiro (Frontiers in Plant Science, 2020)
The heterocysts present in filamentous cyanobacteria such as Anabaena sp. PCC 7120 are known to be regulated by HetN and PatS, the repressors of heterocyst differentiation; therefore, the inactivation of these proteins will result in the formation of multiple heterocysts. To enhance the accumulation of fatty alcohols synthesized in the heterocyst, we introduced mutations of these repressors to increase heterocyst frequency. First, we isolated double mutants of hetN and patS, and confirmed that the null mutation of these genes promoted higher frequencies of heterocyst formation and higher accumulation of heterocyst-specific glycolipids (Hgls) compared with its wild type. Next, we combined hetN and patS mutations with hglT (that encodes glycosyltransferase, an enzyme involved in Hgl synthesis) mutation to increase the accumulation of fatty alcohols, since knockout mutation of hglT results in accumulation of very long chain fatty alcohol, the precursor of Hgl. We also observed retarded growth, lower chlorophyll content, and up to five fold decrease in photosynthetic activity of the hetN/patS/hglT triple mutants. In contrast, the triple mutants showed three times higher heterocyst formation frequencies than the hglT single mutant and wild type. The production rate of fatty alcohol in the triple mutants attained a value 1.41 nmol/mL OD730, whereas accumulation of Hgls in the wild type was 0.90 nmol/mL OD730. Aeration of culture improved the accumulation of fatty alcohols in hetN/patS/hglT mutant cells up to 2.97 nmol/mL OD730 compared with cells cultured by rotation. Our study outlines an alternative strategy for fatty alcohol production supported by photosynthesis and nitrogen fixation.